Hemihyperplasia and tumors. - Cutrone, M. (European Journal of Pediatric Dermatology, 2004)
Clinical features. Hemihyperplasia is a disorder in which one side of the body is at least 5% larger than the other one. The disorder is expression of a defective control of growth. Therefore the associated increased risk of developing a malignant tumor -Wilms, hepatoblastoma, adrenal carcinoma- is not surprising (1, 5, 6). As the prognosis of tumors associated to isolated hemihyperplasia is much better in case of an early diagnosis, in this disorder a clinical, ultrasonographic and biochemical -dosage of alphafetoprotein- periodical screening (2, 3, 4) is indicated. The frequency and the modalities of this screening are not yet established, although its usefulness is clear. This screening is not necessary in hemangiectasic hyperplasia (Klippel-Trenaunay), which is not significantly associated to malignant tumors (3).